Sensitivity analysis of the convective nanofluid flow over a stretchable surface in a porous medium - Khashi’ie, Najiyah Safwa; Mukhtar, Mohd Fariduddin; Hamzah, Khairum; Md Arifin, Norihan; Sheremet, Mikhail; Pop, Ioan (Springer Science and Business Media, 2024)
The aim of the present study is to analyze the nanofluid flow towards a stretching sheet located in a porous medium using both numerical and statistical methods. Another consideration of physical parameters from the standpoint of thermal applications includes the magnetic field and thermal convection. The fluid transport within the porous medium is modeled using the Darcy-Forchheimer-Brinkman equation. Meanwhile, the Tiwari and Das model of nanofluid is adopted where the water is considered as the base fluid and single-walled carbon nanotubes (SWCNTs) as the testing nanoparticles. The local non-similarity (LNS) method is used to transform the partial differential equations (PDEs) into the first and second truncation levels which are then solved using the bvp4c solver. The response surface methodology (RSM) and sensitivity analysis are conducted to highlight the impact and significance of the physical factors like magnetic parameter, nanoparticle’s concentration and Darcy number (porous parameter) to the response (heat transfer). Based on the sensitivity analysis, the response has the largest value when low/minimum usage of magnetic parameter and nanoparticle’s concentration is applied. The thermal rate is not significantly affected by the increment of magnetic parameter but remarkably developed by the upsurge of Darcy number with the use of low nanoparticle’s concentration.